$ω$-Euclidean domain and Laurent series - Romaniv, O.M.; Sagan, A.V. (Carpathian Mathematical Publications, 2016)
It is proved that a commutative domain $R$ is $ω$-Euclidean if and only if the ring of formal Laurent series over $R$ is $ω$-Euclidean domain. It is also proved that every singular matrice over ring of formal Laurent series $R_{X}$ are products of idempotent matrices if $R$ is $ω$-Euclidean domain.